An Unusual Intramolecular Halogen Bond Guides Conformational Selection. Issue 31 (9th July 2018) - Tesch, Roberta; Becker, Christian; Müller, Matthias Philipp; Beck, Michael Edmund; Quambusch, Lena; Getlik, Matthäus; Lategahn, Jonas; Uhlenbrock, Niklas; Costa, Fanny Nascimento; Polêto, Marcelo D.; Pinheiro, Pedro de Sena Murteira; Rodrigues, Daniel Alencar; et al.
Abstract: PIK‐75 is a phosphoinositide‐3‐kinase (PI3K) α‐isoform‐selective inhibitor with high potency. Although published structure–activity relationship data show the importance of the NO2 and the Br substituents in PIK‐75, none of the published studies could correctly determine the underlying reason for their importance. In this publication, we report the first X‐ray crystal structure of PIK‐75 in complex with the kinase GSK‐3β. The structure shows an unusual U‐shaped conformation of PIK‐75 within the active site of GSK‐3β that is likely stabilized by an atypical intramolecular Br⋅⋅⋅NO2 halogen bond. NMR and MD simulations show that this conformation presumably also exists in solution and leads to a binding‐competent preorganization of the PIK‐75 molecule, thus explaining its high potency. We therefore suggest that the site‐specific incorporation of halogen bonds could be generally used to design conformationally restricted bioactive substances with increased potencies. Abstract : Preorganization : The intramolecular Br⋅⋅⋅NO2 halogen bond identified in the phosphoinositide‐3‐kinase inhibitor PIK‐75 likely stabilizes the small molecule in a binding‐competent conformation and reduces the entropic penalty upon binding. This explains the high potency of this inhibitor.